Respuesta :
Answer:
a = 1
b = -1
Step-by-step explanation:
[tex]g(x)=ax^2-b \quad \quad \textsf{(where }\:a\:\textsf{ and }\:b\:\textsf{ are real numbers)}[/tex]
Create 2 equations with b as the subject using the given information.
Equation 1
[tex]\begin{aligned}g(2) &=-5\\\implies a(2)^2-b &=-5\\4a-b &=5\\ b&=4a-5\end{aligned}[/tex]
Equation 2
[tex]\begin{aligned}g(-1) &=2\\\implies a(-1)^2-b &=2\\a-b &=2\\ b &=a-2\end{aligned}[/tex]
Equate the equations and solve for a:
[tex]\begin{aligned}b & =b\\\implies 4a-5 & = a-2\\3a & = 3\\a & = 1\\\end{aligned}[/tex]
Substitute the value of a into Equation 2 and solve for b:
[tex]\begin{aligned}b & =a-2\\a=1 \implies b & =1-2\\b & = -1\end{aligned}[/tex]
Answer:
a = -7/3
b = -13/3
Step-by-step explanation:
Making equations in terms of 'a' and 'b' :
- g(2) = -5 = a(2)² - b ⇒ 4a - b = -5 [Equation 1]
- g(-1) = 2 = a(-1)² - b ⇒ a - b = 2 [Equation 2]
Subtract : Equation 1 - Equation 2
- 4a - b - a + b = -5 - 2
- 3a = -7
- a = -7/3
Finding b :
- -7/3 - b = 2
- b = -7/3 - 6/3
- b = -13/3